Serum creatine phosphokinase as a marker of severity and prognosis in organophosphorus compound poisoning - Nimsarkar, Ashish D.; Atkar, Chandrashekhar M. (International Journal of Advances in Medicine, 2023)
Background: Various newer biomarkers for organophosphorus (OP) compound poisoning are being looked at from diagnostic and prognostic perspectives. The present study was conducted to observe if serum creatine phosphokinase (CPK) can be used as a marker to assess the severity and monitor prognosis in patients of OP compound poisoning. Methods: In this hospital based prospective, observational study, 100 duly screened patients presenting with OP compound were classified as per severity grade according to POP scale. Serum cholinesterase and serum CPK levels were assessed twice, on day 1 and on day 4; apart from requirements as per standard management protocol; and the levels were compared across severity grades of OP compound poisoning. Outcomes such as intermediate syndrome and need of intubation and chances of mortality were studied for correlation. Results: There was statistically significant positive correlation between serum CPK level on day 1 as well as on day 4 with the severity of poisoning. The day 1 mean serum cholinesterase level also increased with the increase in severity of poisoning, but not the day 4 level. Significantly positive correlation was observed between serum CPK levels and development of intermediate syndrome, need of intubation and chances of mortality amongst cases. Conclusions: Serum CPK can be used as an efficient marker of severity in the patients of OP compound poisoning and will be useful to predict prognosis and outcome.